2004
DOI: 10.1093/ndt/gfh288
|View full text |Cite
|
Sign up to set email alerts
|

The worsening of left ventricular hypertrophy is the strongest predictor of sudden cardiac death in haemodialysis patients: a 10 year survey

Abstract: While confirming the role of common CV risk factors for SCD in dialysis patients such as IHD and arterial hypertension, this study is the first to demonstrate that the worsening of LVH is the strongest predictor of sudden death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 26 publications
3
102
0
4
Order By: Relevance
“…Elevated SBP and reduced DBP lead to increased PP, and elevations in PP lead to LVH. 13) Rizzo, et al 14) suggested that elevated ambulatory PP can be considered an effective predictor of cardiovascular risk in hypertensive subjects. In these patients echocardiographic evaluation of LV function and morphology can increase the prognostic value of PP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated SBP and reduced DBP lead to increased PP, and elevations in PP lead to LVH. 13) Rizzo, et al 14) suggested that elevated ambulatory PP can be considered an effective predictor of cardiovascular risk in hypertensive subjects. In these patients echocardiographic evaluation of LV function and morphology can increase the prognostic value of PP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we investigated the pulse pressure (PP) and plasma endothelin (ET)-1 level. It is well known that PP is associated with LVH [13][14][15] and diastolic dysfunction. 12,16) Increased ET-1 production has unfavorable effects on the arterial walls, 17) and endothelial dysfunction is related to the LVH and diastolic function.…”
mentioning
confidence: 99%
“…Two distinct patterns of LV remodelling are seen in CKD patients: concentric LVH, resulting from pressure overload, as seen with hypertension [83,100], and eccentric LVH that is related to volume overload, sodium retention and anaemia [83]. LVH leads to a decreased coronary reserve and arrhythmias [101], which, in turn, are responsible for a disturbing 1,000-fold increase in cardiovascular mortality in CKD stage 5 patients [59].…”
Section: Anaemiamentioning
confidence: 99%
“…A chronic state of volume and pressure overload is a major contributor [2][3][4][5] leading to hypertension, left ventricular hypertrophy [6][7][8][9][10], and death [11,12]. Considerable research has evaluated the effect of dialysis frequency and duration on clinical outcomes [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%